Synthesis of Samarium-Cobalt Sub-micron Fibers and Their Excellent Hard Magnetic Properties - Lee, Jimin; Hwang, Tae-Yeon; Kang, Min Kyu; Cho, Hong-Baek; Kim, Jongryoul; Myung, Nosang V.; Choa, Yong-Ho (Frontiers in Chemistry, 2018)
High-throughput synthesis of Samarium-Cobalt sub-micron fibers with controlled composition and dimension was demonstrated by combining electrospinning and reduction-diffusion processes. The composition of fibers was readily varied (8 < Sm < 20 at.%) by adjusting precursor composition whereas the diameter of fibers was precisely controlled by varying electrospinning parameters (e.g., applied voltage, solution feed rate, temperature, and humidity) to reach single-domain size. X-ray diffraction patterns confirmed that single phase Sm2Co17 fibers were synthesized when the metal precursor ratio (Sm3+/(Sm3++Co2+)) was precisely controlled at 10.6%, whereas mixed phases (i.e., Co-Sm2Co17 or Sm2Co17-Sm2Co7) were observed when the ratio is deviated from the stoichiometric. Magnetic saturation (Ms) of the synthesized fibers monotonically decreased with an increased in Sm content. In contrast, coercivity (Hci) monotonically increased with an increase in Sm content.